Dropout Cause of Elementary School Children in West Java, Indonesia: A Descriptive Study from The Academic-Economic Perspective, and Its Relation to The Pandemic - Hana Riana Permatasari (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This study aims to identify the dropout cause of elementary school children in West Java, Indonesia, especially from the academic and economic perspective. Method: The method used is a descriptive study by distributing an online questionnaire on the relation of schools having dropout children in elementary and junior high school in West Java, Indonesia. Results: The study results show that the reasons for dropouts are the pandemic condition, the environment, laziness, and there is no budget for the school. Most children who dropped out of school during the pandemic stated that learning was not fun, most children desire to return to school, and most dropout children are girls. Most of the dropout families are in the lower middle-class economy. Novelty: The study explained the dropout cause of elementary school in West Indonesia using primary data, which contained the academic and economic factors and their relation to the pandemic that the other previous studies have not revealed.